Dysregulated RASGRP1 expression through RUNX1 mediated transcription promotes autoimmunity. Issue 2 (16th November 2020) - Baars, Matthijs J.D.; Douma, Thera; Simeonov, Dimitre R.; Myers, Darienne R.; Kulhanek, Kayla; Banerjee, Saikat; Zwakenberg, Susan; Baltissen, Marijke P.; Amini, Mojtaba; de Roock, Sytze; van Wijk, Femke; Vermeulen, Michiel; et al.
Abstract: RasGRP1 is a Ras guanine nucleotide exchange factor, and an essential regulator of lymphocyte receptor signaling. In mice, Rasgrp1 deletion results in defective T lymphocyte development. RASGRP1 ‐deficient patients suffer from immune deficiency, and the RASGRP1 gene has been linked to autoimmunity. However, how RasGRP1 levels are regulated, and if RasGRP1 dosage alterations contribute to autoimmunity remains unknown. We demonstrate that diminished Rasgrp1 expression caused defective T lymphocyte selection in C57BL/6 mice, and that the severity of inflammatory disease inversely correlates with Rasgrp1 expression levels. In patients with autoimmunity, active inflammation correlated with decreased RASGRP1 levels in CD4 + T cells. By analyzing H3K27 acetylation profiles in human T cells, we identified a RASGRP1 enhancer that harbors autoimmunity‐associated SNPs. CRISPR‐Cas9 disruption of this enhancer caused lower RasGRP1 expression, and decreased binding of RUNX1 and CBFB transcription factors. Analyzing patients with autoimmunity, we detected reduced RUNX1 expression in CD4 + T cells. Lastly, we mechanistically link RUNX1 to transcriptional regulation of RASGRP1 to reveal a key circuit regulating RasGRP1 expression, which is vital to prevent inflammatory disease. Abstract : Reduced RASGRP1 expression prompts aberrant positive thymocyte selection and antinuclear antibodies in mice. Moreover, patients CD4 + T cells express low RASGRP1 in active autoimmune inflammatory conditions. We show that RUNX1 regulates RASGRP1 transcription via an auto‐immunity associated enhancer, implicating that aberrant regulation of RASGRP1 expression promotes mechanisms of autoimmune pathology.